1992
DOI: 10.1080/00268979200101881
|View full text |Cite
|
Sign up to set email alerts
|

The hexagonal phase of sulfur hexafluoride by molecular dynamics simulation of free clusters

Abstract: The low temperature structures of sulfur hexafluoride have been investigated by molecular dynamics (MD) simulation, using the free duster method. Clusters containing 229 molecules and having an initial BCC structure can transform either into a stable monoclinic structure identical to that of the bulk material or into an hexagonal structure, depending on the cooling procedure. The hexagonal phase is stable, in the MD time scale, below 65 K. In the range of 70-85 K it experiences a spontaneous transformation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…A promising alternative path in nucleation research, and one which does enable the detailed behavior of the molecules to be monitored, is the computer simulation of cooling clusters by molecular dynamics (MD) techniques. If a realistic intermolecular interaction function can be constructed, it is possible to follow the molecular trajectories that lead to nucleation. Indeed, many MD investigations of phaselike changes in extremely small clusters of atoms have already been made, and several have been carried out on clusters of polyatomic molecules. , Quite a few have also been performed on the freezing of bulk atomic systems . As shown in a classic paper by Swope and Andersen, however, artifacts arising from the imposition of periodic boundary conditions have distorted conclusions derived from most simulations of the freezing of bulk systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising alternative path in nucleation research, and one which does enable the detailed behavior of the molecules to be monitored, is the computer simulation of cooling clusters by molecular dynamics (MD) techniques. If a realistic intermolecular interaction function can be constructed, it is possible to follow the molecular trajectories that lead to nucleation. Indeed, many MD investigations of phaselike changes in extremely small clusters of atoms have already been made, and several have been carried out on clusters of polyatomic molecules. , Quite a few have also been performed on the freezing of bulk atomic systems . As shown in a classic paper by Swope and Andersen, however, artifacts arising from the imposition of periodic boundary conditions have distorted conclusions derived from most simulations of the freezing of bulk systems.…”
Section: Introductionmentioning
confidence: 99%
“…Swope and Andersen also confirmed that the behavior of the system during the freezing of atomic liquids in MD simulations closely conformed to the behavior postulated by the classical theory of homogeneous nucleation. Although a number of reports of melting of molecular systems have appeared, ,, virtually no reports of successful MD simulations of the freezing of such systems by unequivocally homogeneous nucleation have been published to date. To bypass the interference associated with periodic boundary conditions when moderately small systems are studied, and to avoid the penalty of working with truly large systems, it has been found advantageous to carry out simulations upon clusters whose boundaries are free.…”
Section: Introductionmentioning
confidence: 99%
“…The exp-6b field adopted the fluorine parameters of Williams and Houpt 18 and Caillat's tellurium parameters. The LJF field used the parameters of Pawley and co-workers who modeled the potential energy between SF 6 molecules solely in terms of interactions between fluorine sites. Values of the parameters for all of the fields, exclusive of the charges, are listed in Table . Parameters are defined by the expressions for Buckingham functions and for Lennard-Jones functions.…”
Section: Methodsmentioning
confidence: 99%
“…The indices α and β denote either a fluorine or a tellurium atom. The values for σ αβ and ε αβ are chosen to be [9]:…”
Section: Computational Detailsmentioning
confidence: 99%
“…In many cases, the form observed in a supersonic jet depends upon the conditions of expansion [9]. Very small clusters are molten at much lower temperatures than the bulk melting point [12].…”
Section: Introductionmentioning
confidence: 99%